2003
DOI: 10.1038/sj.ijir.3901012
|View full text |Cite|
|
Sign up to set email alerts
|

Relation of C-reactive protein and other cardiovascular risk factors to penile vascular disease in men with erectile dysfunction

Abstract: Erectile dysfunction (ED) may be an early sign or symptom of cardiovascular disease (CVD). We examined the relation of traditional and emerging risk factors for CVD to the severity of penile vascular disease in men with ED and without clinical coronary artery disease (CAD). In total, 137 men with ED were evaluated for penile vascular disease severity by penile Doppler ultrasound. These men were divided into the following groups based on ultrasound results: normal, cavernous venous occlusive disease, mild arter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
16
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(21 citation statements)
references
References 20 publications
3
16
0
Order By: Relevance
“…Hence, it could be speculated that penile Doppler ultrasound examination detects vascular dysfunction in a very early stage. 10 These results are in accordance with previous reports of normal rigidometric parameters in patients with reduced dynamic peak systolic velocity at Doppler examination. 37 It should also be observed that the use of drugs potentially interfering with sexual function 21 increases with advancing age with the increase of prevalence of comorbid condition.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Hence, it could be speculated that penile Doppler ultrasound examination detects vascular dysfunction in a very early stage. 10 These results are in accordance with previous reports of normal rigidometric parameters in patients with reduced dynamic peak systolic velocity at Doppler examination. 37 It should also be observed that the use of drugs potentially interfering with sexual function 21 increases with advancing age with the increase of prevalence of comorbid condition.…”
Section: Discussionsupporting
confidence: 83%
“…These data suggest a greater impact of vascular lesions in the pathogenesis of ED in elderly patients, confirming previous reports. 3,5,9,10,11,32 In fact, in our series, basal and dynamic peak systolic velocity at penile Doppler ultrasound examination are inversely correlated with age, as previously described. 5,36 It is noteworthy that, in our sample, the reduction of Doppler parameters is evident from the age of 40 y onwards; a previous study on a small sample of patients showed an even earlier decline of dynamic peak systolic velocity with age, which was evident from the age of 30 y.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…59 Additionally, reduced CRP levels, due to sustained lifestyle changes, may contribute to amelioration of erectile function, as increased CRP Obesity, the metabolic syndrome, and sexual dysfunction K Esposito and D Giugliano levels correlate significantly with reduced NO availability 60 and increasing severity of penile vascular disease as measured by penile Doppler. 61 Moreover, consistent findings support a predictive role of CRP for cardiovascular events in different populations. 62 Rapidly evolving work now demonstrates that in addition to being a marker on innate immunity, CRP also has several direct effects at the level of vessel wall.…”
Section: The Epidemiology Of Sexual Dysfunctionsupporting
confidence: 61%
“…Of these markers, hsCRP is clearly associated with cardiovascular risk, and thus a higher hsCRP value correlates with a higher cardiovascular risk [3]. In addition, several different studies have been conducted that show an association between hsCRP levels and ED [4,5]. …”
Section: Introductionmentioning
confidence: 99%